Determinants of Nepal's Export Trade Instability (Economic Journal of Nepal, 2015)
Fluctuation in export earnings is a great concern to policy makers and can be caused by many factors. This study has analyzed the causes of export instability from 1980/81 to 2012/13 based on secondary data. Using Ordinary Least Square technique the empirical result shows that there is positive relationship between export instability index and three independent variables: commodity concentration index, geographic concentration index and openness index with coefficient of 1.619, 1.163, and 6.023 respectively. Furthermore, it again establishes the negative relationship between export instability index and four independent variables: consumption ratio, food ratio, instability index of real agricultural GDP and instability index of real nonagricultural GDP having co-efficient of -2.922, -7.633, -5.169, and -0.474 respectively.